Bangla Plural Classifiers*. (January 2014) - Dayal, Veneeta
This paper investigates the expression of plurality in Bangla. Like other languages that use classifiers in cardinal constructions, Bangla does not mark the singular–plural distinction on the noun. However, like other classifier languages, Bangla has expressions that convey reference to pluralities: -gulo and -ra . The first can combine with nouns that denote animate as well as inanimate entities, while the other only combines with animate nouns. The first entails reference to more than one entity, while the other seems to merely implicate plural reference. The first is incompatible with kind reference but the other is, for the most part, the preferred form for reference to kinds. A formal account of their semantics is provided, analyzing them both as classifiers and relating them to an analysis of the basic classifier -TA used in cardinal constructions.